Optymiści i pesymiści w sytuacji kryzysów gospodarczych (na przykładzie kryzysów gospodarczych Rosji) - Optimists and pessimists in the economic crisis (based on the economic crisis in Russia) - Vodopyanova, Natalia E.; Chesnokov, Vładimir B. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Optimism and pessimism as two different positions in life have been presented; life position defined as a subjective attitude of a man to the social reality, which contains the values and attitudes. The objective component of the position is the multiplicity of actions and strategies of behaviour in emergency situations. Optimism is understood as a system construct conditioning the choice of active coping strategies behaviour. Behavioural differences between optimists and pessimists in emergencies related to subjective evaluation and the prediction of emergency duration have been shown. The technologies of psychological monitoring of entities working in emergency situations, based on the strengthening of individual optimism resources and an active position in life have been proposed.
Keywords: optymizm; pesymizm; czynna pozycja życiowa; zachowania zaradcze; sytuacje kryzysowe; monitoring psychologiczny; optimism; pessimism; an active position in life; constructive behaviour; emergencies; psychological monitoring